Special self-compacting concretes - Stanciu, Darius (2013)
The paper presents experimental investigations on the special self-compacting concretes, in different compositions. Also, in this paper highlights the influence of super plasticizers additives use upon the mechanical, structural and chemical properties of selfcompacting concretes improving. During these laboratory investigations were made samples of self-compacting concrete with diferente compositions, on which were performed workability and mechanical tests (compressive strength), as well as, structural attempts (microscopy, density, porosity tests).